THE INFLUENCES OF Fe(III) ION and Fe(OH)3 COLLOID ON THE PHOTODEGRADATION of p-CHLOROPHENOL CATALYZED BY TiO2 - Endang Tri Wahyuni; Mudasir Mudasir; Ngatidjo Hadipranoto (Universitas Gadjah Mada, 2006)
The influences of ionic Fe(III) and colloidal Fe(OH)3 on the effectiveness of p-chlorophenol photodegradation catalyzed by TiO2 has been studied. Photodegradation was carried out in a batch system by irradiating a suspension of TiO2, p-chlorophenol, and Fe(III) as ionic or colloidal forms, using UV lamp for a period of time accompanied by magnetic stirring. Concentration of photodegraded p-chlorophenol was calculated by subtracting the initial concentration with that of undegraded p-chlorophenol. Concentration of undegraded p-chlorophenol was determined by gas chromatography. In this study, TiO2 mass and the photodegradation time were optimized. The influences of concentration of Fe(III) solution, mass of Fe(OH)3, and pH of the solution have also been systematically studied. The research results showed that the presence of Fe(III) ions improved the effectiveness of photocatalytical degradation of p-chlorophenol, which was proportional to the concentrations of Fe(III) ion. In contrast, the increasing mass of Fe(OH)3 led to a decrease in the degree of p-chlorophenol photodegradation. Furthermore, it was observed that increasing pH of the solution resulted in a decrease in the photodegradation of p-chlorophenol. This phenomena may be due to the different species of TiO2 available at the surface of photocatalyst and of ionic Fe(III) and colloidal Fe(OH)3 in the solution resulted from the pH alteration. The highest photodegradation degree, ca. 80 % was obtained when 20 mg of TiO2 was applied in the photodegradation of 50 mL of 100 ppm p-chlorophenol solution in the presence of 100 ppm Fe3+ irradiated by UV-light for 25 hours.